The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.jpcc.1c08474
|View full text |Cite
|
Sign up to set email alerts
|

Friedländer, Knoevenagel, and Michael Reactions Employing the Same MOF: Synthesis, Structure, and Heterogeneous Catalytic Studies of ([Zn(1,4-NDCA)(3-BPDB)0.5]·(DMF)(MeOH) and [Cd4(1,4-NDCA)4(3-BPDB)4]·2(DMF)

Abstract: Friedlander, Knoevenagel, and Michael Reactions Employing the Same MOF: Synthesis, Structure, and Heterogeneous Catalytic Studies of ([Zn(1,4-NDCA)(3-BPDB) 0.5 ]•(DMF)(MeOH) and [Cd 4 (1,4-NDCA) 4 (3-BPDB) 4 ]•2(DMF) Published as part of The Journal of Physical Chemistry virtual special issue "Kankan Bhattacharyya Festschrift".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 96 publications
1
6
0
Order By: Relevance
“…By contrast, electron-donating groups such as −OCH 3 could effectively hinder the reaction (entries 3–5). The substrate of p -(4-methylphenoxy)­benzaldehyde dimethyl acetal gave a obviously lower conversion (88%, entry 6), which should be attributed to the fact that the large substituent greatly affected the mass transfer of the whole molecule in the pores (Table S5), consistent with related reported MOF-based catalysts. The 1 H NMR spectra of all the above tandem deacetalization-Knoevenagel condensation products could be found in Figures S16–S22. All in all, this series of catalytic experiments demonstrated that NUC-54a was a highly promising bifunctional catalyst for deacetalization-Knoevenagel condensations with satisfactory product yield and high selectivity. …”
Section: Resultssupporting
confidence: 77%
“…By contrast, electron-donating groups such as −OCH 3 could effectively hinder the reaction (entries 3–5). The substrate of p -(4-methylphenoxy)­benzaldehyde dimethyl acetal gave a obviously lower conversion (88%, entry 6), which should be attributed to the fact that the large substituent greatly affected the mass transfer of the whole molecule in the pores (Table S5), consistent with related reported MOF-based catalysts. The 1 H NMR spectra of all the above tandem deacetalization-Knoevenagel condensation products could be found in Figures S16–S22. All in all, this series of catalytic experiments demonstrated that NUC-54a was a highly promising bifunctional catalyst for deacetalization-Knoevenagel condensations with satisfactory product yield and high selectivity. …”
Section: Resultssupporting
confidence: 77%
“…The α-Po structure is common in many MOF structures (Figure 3). 8,[13][14][15][16][17]73 For the topological analysis, the Mn(1) dimers and Cu 6 S 6 units were considered as two distinct nodes. The connectivity between the Mn(1) dimers and Cu 6 S 6 units gives rise to a uninodal net with a α-Po topology.…”
Section: Structure Of [{Cu 6 (Mna )6 }{Mn(bpy)h 2 O} 2 {Mn(h 2 O) 4 }...mentioning
confidence: 99%
“…34,64−69 In our earlier efforts by employing compounds having Cu 6 S 6 clusters and other building units, we have explored catalytic reactions that utilize both the Lewis acidic as well as basic sites. 30,73 In the present study, we have attempted a multicomponent Hantzsch reaction (Scheme 3). For this, aromatic aldehyde, ethyl acetoacetate, indandione, and ammonium For undertaking the catalytic reaction, the needed reaction conditions and parameters were first optimized.…”
Section: Structure Of [{Cu 6 (Mna )6 }{Mn(bpy)h 2 O} 2 {Mn(h 2 O) 4 }...mentioning
confidence: 99%
See 1 more Smart Citation
“…This approach would make the overall reaction simpler and cost-effective. The important criterion for developing a catalyst that can favor a cascade/tandem reaction is to have multifunctionality within the same catalyst. In addition, it is preferable to have such multifunctional catalytic centers that are separated spatially. Such an arrangement would help to reduce any undesirable interactions between the reacting chemical species and help in the formation of the final product.…”
Section: Introductionmentioning
confidence: 99%